Influence of Artichoke Antioxidant Activity in Their Susceptibility to Suffer Frost Injury - Marina Giménez-Berenguer; María Gutiérrez-Pozo; Vicente Serna-Escolano; María José Giménez; Pedro Javier Zapata (MDPI AG, 2023)
In the northern hemisphere countries, artichoke harvest occurs in winter months; consequently, they are exposed to cold temperatures. This can lead to frost injury, such as triggering the blistering of the cuticle and detachment of outer bracts, which eventually could display brown or black discolouration. This can cause major economic and production losses. As far as we know, no literature is available about this problem in artichokes. Thus, the main aim of this study was to evaluate the effect of total phenolic content and the antioxidant potential of 'Blanca de Tudela' artichokes in their capacity to tolerate frost injury when they are exposed to low temperatures. Several factors were analysed, including floral head order, weight and size of artichokes, total phenolic content, phenolic profile and total antioxidant activity. Results showed that tertiary heads, which are the smallest in size, exhibited a greater amount of total phenolic content and antioxidant activity. As a result, these characteristics offered enhanced protection to the artichoke against frosting temperatures. In contrast, the largest artichokes, especially the primary heads, were more susceptible to suffer frostbite. Therefore, artichokes with robust antioxidant systems, characterized by elevated phenolic content, are crucial to reduce their susceptibility to frost injury.